Intoleransi dan Radikalisme Agama: Konstruk LSM tentang Program Deradikalisasi - Supriadi, Endang; Ajib, Ghufron; Sugiarso, Sugiarso (JSW (Jurnal Sosiologi Walisongo), 2020)
Reformation-era opened the opportunities for political freedom and the development of religious life among the Islamic community in Indonesia. It can be seen in the strengthening of the identity and the movements of religious groups outside the mainstream religious groups, namely radicalism. Acceptance of different narratives based on religious sentiments is shown in the public space by building a distinction between "us" and "them". There is a need for an antidote toward radical understanding that resulted in acts of terror naming the deradicalization. By qualitative methods, this study indicated that during the nine years of the establishment of the National Counterterrorism Agency (BNPT) the programs are still static because the program has not been able to minimize or even eliminate radical understanding that led to acts of terror. All elements of civil society must strengthen the deradicalization program of BNPT. Both NGOs (Wahid Institute and SETARA Institute) stated that the process of deradicalization was not only on individual problems, but the social environment also played an active role. It is the state that has the ability in the process of deradicalization, but the state must involve civil society.